The Dragon’s Deal: Sino-African Cooperation in Higher Education - Obamba, Milton (International Higher Education, 2013)
China and Africa have a long tradition of bilateral cooperation. The establishment of the Forum on China-Africa Cooperation (FOCAC) in 2000 has dramatically revolutionized Sino-African cooperation. It is an intergovernmental agency established jointly by China and African countries to provide a plan for strengthening bilateral cooperations between China and 50 African member countries. The emergence of FOCAC can be more accurately interpreted as part of the increasing institutionalization and intensification of Sino-African relations, at a time of deepening multilateral interactions, although critiques have intensified simultaneously.